Physical Activity, Outdoor and Adventure Sports During the Covid-19 Pandemic Process - Burak Gürer; Mürsel Biçer (Lithuanian Sports University, 2022)
The COVID-19 pandemic has created unprecedented chaos worldwide in the current century. Thousands of people died, and millions of people caught the COVID-19 virus. In this tough time, people locked themselves down in their homes for a long time, either voluntarily or mandatorily as part of governmental precautions against the rapid spreading of the virus. This difficult time forced people to change their daily life routines to a sedentary life which affected them mentally and psychologically. Following the lifting of the restrictions, people have started to make an intense effort to do physical activity and spend more time in nature to relax. Consequently, physical activity in a safe environment has become a priority for most people. With this challenging period, open spaces have become more preferred areas for physical activity rather than closed areas. Outdoor and adventure sports have started to consider the safest way of physical activity. Intense physical activity can be done in outdoor and adventure sports, depending on the type of activities. With the necessary precautions taken during the activities, doing outdoor and adventure sports has become a critical step in reducing the effects of mental and psychological factors such as stress, pessimism, bad mood, and unhappiness. Moreover, these sports physically contribute positively to lung capacity. This study provides useful information about outdoor and adventure sports along with highlighting important points and possible risks when doing physical activity in open spaces during the COVID-19 pandemic.   Keywords: adventure sports, COVID-19, physical activity, outdoor sports.